POTENTIAL OF HUNTING TOURISM IN THE MIDDLE BANAT - Mrkša, Milutin M (International Journal of Economic Practice and Policy, 2015)
The aim of this paper is to present the potential of hunting tourism in the Middle Banat in the promotion and advancement of this particular form of tourism activities. Hunting is one of the most economically important form of tourism activities because in addition to the regular services of transportation, lodging and hunting licenses, tourists pay for a hit-and-miss), a meat and a trophy. With the aim of presenting the potential in a quality manner, special attention will be paid to hunting clubs, hunting grounds and accommodation facilities, which are in addition to the human sector, the most important factor in hunting tourism.